Islanders' educational choice: Determinants of the students' performance in the Cambridge International Certificate Exams in the Republic of Maldives. (March 2015) - Yamada, Shoko; Fujikawa, Kiyoshi; Pangeni, Krishna P.
Abstract: This paper is based on the analysis of a questionnaire survey with teachers and 10th-grade students who took the Cambridge Ordinary Level (O-level) and national secondary school certificate (SSC) examinations in mathematics, English, and Divehi language in the Republic of Maldives. A total of 517 students and 60 subject teachers from eight schools took part in this survey, and the responses from students were matched up with their examination scores in three subjects. The primary objective of this paper is to identify the factors influencing the students' performance in three subjects. Based on that, it considers the implications of employing an international examination system to certify students of the national education system in Maldives. Because of the limited capacity in running a mass education system, this small island state uses an externally-developed examination system for many years. However, the study reveals that the students' performance in O-level exams largely depends on the households' socio-economic conditions and learning environment at home. Factors related to teachers and teaching–learning processes in school do not have much impact. While the government is reforming the curriculum to be more learner-centered and relevant to the national context, the externally-developed exams conflict with such drive for nationalization and widen the gap of educational outcomes among students with and without extra support from the family.